The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1046/j.1469-7580.2000.19620243.x
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement of extracellular matrix during cluster formation by human luteinising granulosa cells in culture

Abstract: Human ovarian granulosa cells were cultured on a basement membrane preparation (Matrigel) to investigate the role of extracellular matrix components in granulosa cell cluster formation. Time-lapse videomicroscopy of these cultures revealed a rapid aggregation of cells which was initiated during the first 2-4 h of culture so that by 8 h most of the granulosa cells were incorporated into clusters. Further amalgamation then occurred with the transfer of cells along 'bridges' between combining clusters. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 10 publications
(9 reference statements)
0
14
0
Order By: Relevance
“…The demonstration of both FSHR and Coll IV in GCs cultured in 3D suggested that this culture system mimics physiological ovarian follicular development (Figure 1). Similar experiences were made earlier when whole ovarian follicles were cultured in vitro [9, 56, 6164]. In a 3D culture system with intact murine follicles collagen type I promoted an increase in size of two-layered follicles but had no effect on multilayered follicles [9].…”
Section: Granulosa Cells Phenotype In Accordance To Neofolliculogementioning
confidence: 57%
“…The demonstration of both FSHR and Coll IV in GCs cultured in 3D suggested that this culture system mimics physiological ovarian follicular development (Figure 1). Similar experiences were made earlier when whole ovarian follicles were cultured in vitro [9, 56, 6164]. In a 3D culture system with intact murine follicles collagen type I promoted an increase in size of two-layered follicles but had no effect on multilayered follicles [9].…”
Section: Granulosa Cells Phenotype In Accordance To Neofolliculogementioning
confidence: 57%
“…Also, in the present study, the basement membrane did not change in thickness or appearance as the follicles grew in size suggesting that the basement membrane is continuously being remodeled. Recent studies suggest that the extracellular matrix can be actively rearranged by granulosa cells in vitro (Richardson et al, 2000). Since basement membranes are specialized extracellular matrices, it is possible that the basement membrane around the ovarian follicles is rearranged by granulosa cells in vivo too.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably mediated through their gap junction cytoplasmic connections to the ooplasm (Carabatsos et al, 2000), which traverses the zona pellucida, as well as by the cumulus mass exerting a modulatory effect on the microenvironment surrounding the immature oocytes (Byskov et al, 1997;McNatty et al, 1980); which could be important if the in vitro culture conditions are suboptimal. Indeed, both Hwang et al (2000) and Richardson et al (2000) observed in their studies that human granulosa cells appear to cluster together and to have a more differentiated morphology in the presence of ECM. The next step of the study would be to investigate the use of coculture to improve the meiotic competence of such putatively 'less competent' GV oocytes from the mouse.…”
Section: Discussionmentioning
confidence: 96%
“…This is expected from previous studies with different species, which have all shown that the surrounding cumulus cells have an important part to play in the oocyte meiotic maturation process (Gilula et al, 1978;Voznesenskaia et al, 2001). Hwang et al (2000) and Richardson et al (2000) reported that the in vitro culture of human granulosa cells on ECM probably mimicked the physiological situation in vivo, in which sheets of granulosa cells are attached to the basement membrane within the follicle. The use of naked or partially naked immature GV oocytes could also make this study more relevant to the human clinical assisted reproduction model, in which a substantial number of naked or partially naked oocytes are routinely obtained by follicular aspiration or upon denudation of the cumulus mass for intracytoplasmic sperm injection (ICSI).…”
Section: Discussionmentioning
confidence: 99%